2019
DOI: 10.1021/acs.jafc.9b06064
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation and Risk Assessment of Multiresidual Fungicides in Grapes under Field Conditions

Abstract: Grapes are among the most popular fruits globally, and various fungicides are widely applied to grape crops. As such, the presence of multiple fungicide residues and dietary risks in grapes has become the focus of significant attention. In this study, an easy-to-implement and sensitive UPLC-MS/MS approach was developed to simultaneously determine pyraclostrobin, dimethomorph, cymoxanil, cyazofamid and its metabolite CCIM in grapes via QuEChERS. This approach achieved 78.1–106.0% recovery and a 0.01 mg kg–1 lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…In this study, fungicide application was carried out after pruning; i.e., in winter when the vine was dormant and biological activity was less intense than during the growing season when treatments are carried out (leaves and grapes present). In some studies, some fungicides applied to grapes in the field during the summer period were found to have dissipated before harvest (Nadeem et al, 2020;Yang et al, 2020). In the present study, however, there was a higher concentration of the studied active substances (trifloxystrobin, boscalid, kresoxim-methyl and penconazole) in the vine-shoots to which they had been applied, since there was no translocation through the plant, and they could therefore not be distributed in order to be eliminated afterwards (as would have been the case if the treatments had been applied to the grapes).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, fungicide application was carried out after pruning; i.e., in winter when the vine was dormant and biological activity was less intense than during the growing season when treatments are carried out (leaves and grapes present). In some studies, some fungicides applied to grapes in the field during the summer period were found to have dissipated before harvest (Nadeem et al, 2020;Yang et al, 2020). In the present study, however, there was a higher concentration of the studied active substances (trifloxystrobin, boscalid, kresoxim-methyl and penconazole) in the vine-shoots to which they had been applied, since there was no translocation through the plant, and they could therefore not be distributed in order to be eliminated afterwards (as would have been the case if the treatments had been applied to the grapes).…”
Section: Discussionmentioning
confidence: 99%
“…For acute dietary risk assessment, the international estimation of short-term intake (IESTI) should not be greater than the acute reference dose (ARfD) in order to protect the health of consumers. 34 The formulas to calculate IESTI and %ARfD are as follows 35 U HR v LP U HR bw…”
Section: Methodsmentioning
confidence: 99%
“…The formulas to calculate IESTI and %ARfD are as follows where U (kg) is the weight of the edible portion of a single apple, HR (mg/kg) is the highest residue in the edible portion of the apple, v is the variability factor, LP (kg) is the large portion, and bw is the average body weight of the population subgroups. v is 3 for apples, and the LP and U values come from the WHO. , …”
Section: Methodsmentioning
confidence: 99%
“…During the grape cultivation period, it is common practice in vineyards to use pesticides, such as fungicides, insecticides and herbicides, to obtain high production. Grapes receive multiple doses of pesticides, which may partly transfer into wine [4][5][6][7][8]. In previous market surveillance studies [9][10][11][12][13], metalaxyl, procymidone, fenhexamid, cyprodinil, azoxystrobin and iprodione were detected in commercial grape wines; tebuconazol, metalaxyl and cyprodinil represent the most frequently detected pesticides.…”
Section: Introductionmentioning
confidence: 93%